2022
DOI: 10.3390/su14095391
|View full text |Cite
|
Sign up to set email alerts
|

What Do the Public Want to Know about Farming and Why? Findings from a Farmer-Initiated Public Consultation Exercise in Ireland

Abstract: With advances in information communication technologies and sustainability-driven changes in consumer behavior, farmer–citizen communication is a communicative dyad that is receiving attention. Farmers and citizens view farming practices through very different lenses of prior knowledge, experiences, beliefs, and values, presenting unique communication challenges. Dialogue-based communication can help to build empathy and trust. Initiated by a committee of farmers, a public consultation exercise was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(97 reference statements)
1
3
0
Order By: Relevance
“…This article highlights the value of public engagement focused upon food and farming, and it suggests a need for more. This has been reaffirmed in subsequent FIELD activities, and highlighted elsewhere (Regan and Kenny, 2022). Given previous criticisms of a lack of communication and transparency surrounding farming issues (Murphy-Lawless, 2004), and the relative lack of public input in the Agriculture Bill (DEFRA, 2018(DEFRA, , 2020, our findings show that more engagement would be welcomed.…”
Section: Discussionsupporting
confidence: 74%
“…This article highlights the value of public engagement focused upon food and farming, and it suggests a need for more. This has been reaffirmed in subsequent FIELD activities, and highlighted elsewhere (Regan and Kenny, 2022). Given previous criticisms of a lack of communication and transparency surrounding farming issues (Murphy-Lawless, 2004), and the relative lack of public input in the Agriculture Bill (DEFRA, 2018(DEFRA, , 2020, our findings show that more engagement would be welcomed.…”
Section: Discussionsupporting
confidence: 74%
“…Considering that public concern for farm animal welfare is increasing (Alonso et al 2020 ), it seems unlikely excluding the public voice from such discussions will be socially sustainable. Indeed, a recent study by Regan and Kenny ( 2022 ) found that members of the public expressed a desire for increased and two-way engagement with farmers.…”
Section: Resultsmentioning
confidence: 99%
“…However, many participants in the focus groups were 20 reflective in their critique of farm practices and farmers; many indicated that they were empathetic towards the situation of farmers -citing difficulties to making seismic changes to husbandry practices on farms to reduce reliance on antibiotics. This could be a particular reflection of the geographical context of the current study, given that consumers tend to associate livestock farming in Ireland with small, pasture-based family-farms (Regan & Kenny 2022). Future research should consider cross-cultural differences in social representations of antibiotics and farming, particularly considering aspects of identity and blame attribution.…”
Section: Discussionmentioning
confidence: 98%